Oil Crops of the world - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
'Oil Crops of the World: their breeding and utilization', edited by Gerhard Robbelen, R Keith Downey, Amram Ashri, ISBN 0 07 0530815